2007
DOI: 10.37236/963
|View full text |Cite
|
Sign up to set email alerts
|

Some Properties of Unitary Cayley Graphs

Abstract: The unitary Cayley graph $X_n$ has vertex set $Z_n=\{0,1, \ldots ,n-1\}$. Vertices $a, b$ are adjacent, if gcd$(a-b,n)=1$. For $X_n$ the chromatic number, the clique number, the independence number, the diameter and the vertex connectivity are determined. We decide on the perfectness of $X_n$ and show that all nonzero eigenvalues of $X_n$ are integers dividing the value $\varphi(n)$ of the Euler function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
138
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 10 publications
1
138
0
3
Order By: Relevance
“…Observe that if we set m = 3 in Corollary 3.1, we recover the previously-discovered formula 1 6 nφ(n)S 2 (n) for the number of triangles in G Z/(n) . Our proof of this formula seems much more natural and illuminating than those already in existence [1,2,3]. Before proceeding to uncover some additional properties of generalized totient graphs, we pause to note an interesting divisibility relationship that arises as a corollary of Theorem 3.1.…”
Section: Enumerating Cliques In Generalized Totient Graphsmentioning
confidence: 94%
See 2 more Smart Citations
“…Observe that if we set m = 3 in Corollary 3.1, we recover the previously-discovered formula 1 6 nφ(n)S 2 (n) for the number of triangles in G Z/(n) . Our proof of this formula seems much more natural and illuminating than those already in existence [1,2,3]. Before proceeding to uncover some additional properties of generalized totient graphs, we pause to note an interesting divisibility relationship that arises as a corollary of Theorem 3.1.…”
Section: Enumerating Cliques In Generalized Totient Graphsmentioning
confidence: 94%
“…For this reason, we record the following fact and omit the proof. Another standard result concerning unitary Cayley graphs states that the clique number and the chromatic number of G Z/(n) are both equal to the smallest prime factor of n [2]. Again, the proof generalized in a straightforward manner, so we omit the proof of the next fact.…”
Section: Other Properties Of Generalized Totient Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…in turn, is also the chromatic number of G Z/nZ [23]. Klotz and Sander have also shown that the eigenvalues of G Z/nZ (that is, the eigenvalues of an adjacency matrix of G Z/nZ ) are integers that divide ϕ(n) (in fact, they are given by Ramanujan sums) [23]. Figure 1 depicts the graphs G Z/nZ for 2 ≤ n ≤ 10.…”
Section: Unitary Cayley Graphs and Schemmel Totient Functionsmentioning
confidence: 99%
“…The clique number of G Z/nZ , defined to be the largest integer k such that G Z/nZ has a clique of order k, turns out to be the smallest prime factor of n. This, E-mail address: cdefant@princeton.edu. in turn, is also the chromatic number of G Z/nZ [23]. Klotz and Sander have also shown that the eigenvalues of G Z/nZ (that is, the eigenvalues of an adjacency matrix of G Z/nZ ) are integers that divide ϕ(n) (in fact, they are given by Ramanujan sums) [23].…”
Section: Unitary Cayley Graphs and Schemmel Totient Functionsmentioning
confidence: 99%